2016
DOI: 10.17265/1548-6583/2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Is Earnings Management a Technique to Reduce Cost of Capital? Exploratory Study on Indian Companies

Abstract: Earnings management has attracted lots of academicians towards the research due to the emerging frauds and downfall of great corporate giants of the world. Mainly earnings measurement is based on the accounting estimates which managers can easily manipulate for their self-interest. The study investigates the relationship between cost of capital and the earnings measurement for the Indian firms. Measurement of earnings is mostly computed by taking either discretionary accruals (DAC) or non-discretionary accrual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This result suggests that by using a powerful corporate governance system, by declining the information asymmetry (increasing transparency) and agency conflict, we would be able to enhance the quality of financial reports and by strengthening the capital market and attracting financial suppliers and investors, absorb the required financial resources of the firm by a lower rate. These results are in line with those of Adnan and Qubbaja (2019), Bozec and Bozec (2011), Mazzotta and Veltri (2012), Teti et al (2016), Gupta et al (2018), Zhu (2014), Srivastava et al (2019) and Patro & Kanagaraj (2016), but are in contrast with those of McInnis (2010) and Juniarti and Natalia (2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result suggests that by using a powerful corporate governance system, by declining the information asymmetry (increasing transparency) and agency conflict, we would be able to enhance the quality of financial reports and by strengthening the capital market and attracting financial suppliers and investors, absorb the required financial resources of the firm by a lower rate. These results are in line with those of Adnan and Qubbaja (2019), Bozec and Bozec (2011), Mazzotta and Veltri (2012), Teti et al (2016), Gupta et al (2018), Zhu (2014), Srivastava et al (2019) and Patro & Kanagaraj (2016), but are in contrast with those of McInnis (2010) and Juniarti and Natalia (2012).…”
Section: Discussionsupporting
confidence: 90%
“…These studies indicate good enterprise management will reduce the cost of equity. For example, Adnan and Qubbaja (2019), Bozec and Bozec (2011), Mazzotta and Veltri (2012), Srivastava et al (2019) and Patro & Kanagaraj (2016) showed that there is a negative relationship between corporate governance and cost of equity. Claessens and Yurtoglu (2013) concluded that bettergoverned firms have easier access to external finance in emerging economies, resulting in a lower cost of equity.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Many previous studies related to the cost of capital have been carried out include governance (AlHares, 2020; Arslan, 2019;Khan et al, 2020;Pham et al, 2012), litigation risk (Qin et al, 2020), corporate social responsibility disclosure (Atan et al, 2018;Ellili, 2020;Gjergji et al, 2021;Johnson, 2020;Rahmasari, 2013), economic policy uncertainty (Xu, 2020), risk disclosure (Almania, 2019;Liu, 2020), leverage (Battisti et al, 2020;Rajverma et al, 2019), environmental disclosure (Anh, 2020;Haninun et al, 2019), integrated reporting (Vena et al, 2019), ownership structure (Rajverma et al, 2019), dividend policy (Rajverma et al, 2019), disclosure quality (Ezat, 2019), intellectual capital disclosure (Gomes et al, 2019), employee shareholding (Aubert et al, 2017), information risk (Safdar & Yan, 2016), earnings management (Patro & Kanagaraj, 2016), board of directors concentration (Upadhyay, 2014), excess control (Bozec et al, 2014), and earnings quality (Apergis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%